Impact of the COVID-19 pandemic on intimate partner violence in Sudan, Malawi and Kenya - Salma A. E. Ahmed; Josephine Changole; Cynthia Khamala Wangamati (BMC, 2021)
Abstract The COVID-19 infection control and prevention measures have contributed to the increase in incidence of intimate partner violence (IPV) and negatively impacted access to health and legal systems. The purpose of this commentary is to highlight the legal context in relation to IPV, and impact of COVID-19 on IPV survivors and IPV prevention and response services in Kenya, Malawi, and Sudan. Whereas Kenya and Malawi have ratified the Convention on Elimination of all forms of Discrimination against Women (CEDAW) and have laws against IPV, Sudan has yet to ratify the convention and lacks laws against IPV. Survivors of IPV in Kenya, Malawi and Sudan have limited access to quality health care, legal and psychosocial support services due to COVID-19 infection control and prevention measures. The existence of laws in Kenya and Malawi, which have culminated into establishment of IPV services, allows a sizable portion of the population to access IPV services in the pandemic period albeit sub-optimal. The lack of laws in Sudan means that IPV services are hardly available and as such, a minimal proportion of the population can access services. Civil society's push in Kenya has led to prioritisation of IPV services. Thus, a vibrant civil society, committed governments and favourable IPV laws, can lead to better IPV services during the COVID-19 pandemic period.